Rancang Bangun Mesin Pengupas Kulit Ari Buah Kelapa Menggunakan Metode Verein Deutshcer Ingenieure (VDI) 2222 di PT PECU - Sri Suci Yuniar; Asha Asyita Sundari; Hendro Prassetiyo (Jurnal Teknik Mesin, 2024)
Coconut is a plant that has many benefits and can be utilized as a whole starting from the stem, meat, coir, shell, water, and coconut cuticle. PT Pacific Eastern Coconut Utama (PECU) is the largest coconut processing company in Java Island with its main products, namely liquid (Coco Day and Liquid Coconut Milk) and non-liquid (Desiccated Coconut and Coconut Powder). Before coconuts become final products, namely non-liquid products (Desiccated Coconut and Coconut Powder), these coconuts will go through the process of stripping the coconut cuticle. In this process, PT PECU still uses manual tools which require more time and effort and not all operators have the same abilities. Therefore, companies need to design appropriate tools using the Verein Deutscher Ingenieure 2222 (VDI 2222) method. This method is used to develop and design products, systems or tools by considering various aspects, such as user needs, security and efficiency.The results of this design can help companies to increase company productivity, do not endanger the operator, and the machine can be operated easily.